The Roles and Pharmacological Effects of FGF21 in Preventing Aging-Associated Metabolic Diseases - Yan, Junbin; Nie, Yunmeng; Cao, Jielu; Luo, Minmin; Yan, Maoxiang; Chen, Zhiyun; He, Beihui (Frontiers in Cardiovascular Medicine, 2021)
With the continuous improvement of living standards and the lack of exercise, aging-associated metabolic diseases such as obesity, type 2 diabetes mellitus (T2DM), non-alcoholic fatty liver disease (NAFLD) is becoming a lingering dark cloud on the heads of human. Interestingly, metabolic disorders are related to glycometabolism, lipometabolism, and closely related to cell aging. Such diseases need to be treated systematically. Fibroblast growth factor 21 (FGF21), a member of the FGFs family, can regulate the homeostasis of metabolism, as well as cellular aging. FGF21 can activate autophagy-related genes，improve inflammation, thereby inhibiting cellular aging; FGF21 can also directly activate aging-related genes to achieve the purpose of anti-aging. Besides, FGF21 can regulate glucose and lipid metabolism by controlling metabolism-related genes, such as adipose triglyceride lipase (ATGL) and acetyl-CoA carboxylase (ACC1). FGF21 and analogs of FGF21 are gradually being valued and become a treatment approach for metabolic diseases. However, the mechanism of how FGF21 achieves curative effect is still not exact. This review aims to interpret the interactive influence between FGF21, aging, metabolic diseases and delineate the pharmacology of FGF21.